The Urgency Of Green Ship Recycling Methods And Its Regulations In Indonesia From The International Law Perspective - Bismo Jiwo Agung; Arie Afriansyah (Unram Law Review, 2022)
One of the critical problems for ships utilization is the limited operative life which affect its efficiency. Therefore, ship owners tend to send these ships for recycling. On the one hand, ship recycling industry can absorb labour and become a source of state revenue. Nevertheless, these activities significantly affect the preservation of the marine environment if not appropriately managed. Marine waste pollution is an essential issue in global context. Regrettably, as a country with a massive shipping intensity and geographically a strategic location, Indonesia does not have a comprehensive national policy regarding recycling ships weighing for 500 GT or more. The government allows conventional ship recycling methods that are not environmentally friendly and sustainably, which contradicts Indonesia's commitment to supporting the Sustainable Development Goals (SDGs). Thus, Indonesia is vulnerable to claims regarding poor pollution management due to ship dismantling activities. The claim could be addressed to the state’s responsibility, which refered to international instruments such as conventions and guidelines in terms of preventing pollution to neighboring countries originating from ship breaking and dismantling activities that lack regulation and measures. This article argues the urgency to reform the current national ship recycling regime in the future to apply a greener method by alluding to international general principles, customary and jurisprudence.